1970
DOI: 10.1161/01.res.27.4.513
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Inotropic Interventions on the Dynamic Properties of the Contractile Elements in Heart Muscle of the Cat

Abstract: Force-velocity-length (FVL) relations were obtained by determining die phase-plane tracings of velocity of shortening vs. length during isotonic contractions. These measurements were then replotted in a three-dimensional graph after correction for the series elastic extension during the isometric phase of the contractions as derived from a quick release contraction. On examining the influence of temperature (29° and 37°), preload, frequency of stimulation (12/min and 24-30/min), paired stimulation (PS), calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1971
1971
1998
1998

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…There are also significant differences between the pharmacological responses of atrial and ventricular muscles (15,16). Whereas abundant information is available about the mechanical behavior of ventricular myocardium (15)(16)(17)(18)(19)(20)(21)(22)(23), much less is known about atrial myocardial performance, and conflicting results have been reported (15,16,24). Differences in the reported results may be due in part to considerable species variability (15,16) and in part to the fact that published accounts have often failed to emphasize how the results were obtained under significantly different experimental conditions (15,16).…”
mentioning
confidence: 99%
“…There are also significant differences between the pharmacological responses of atrial and ventricular muscles (15,16). Whereas abundant information is available about the mechanical behavior of ventricular myocardium (15)(16)(17)(18)(19)(20)(21)(22)(23), much less is known about atrial myocardial performance, and conflicting results have been reported (15,16,24). Differences in the reported results may be due in part to considerable species variability (15,16) and in part to the fact that published accounts have often failed to emphasize how the results were obtained under significantly different experimental conditions (15,16).…”
mentioning
confidence: 99%
“…The influence of Ca on the mechanical performance of isolated skinned and glycerinated fibers of skeletal muscle has been studied recently (1,(3)(4)(5)(6)(7)(8)(9). Potentiating effects of Ca on the contractile properties of isolated intact cardiac muscle have been observed (10,11); some investigators suggest that Ca augments force development (P o ) and maximum shortening velocity (Vmax) extrapolated from force-peak velocity relations of afterloaded contractions (10,12), but such derivations of Vmax are subject to methodological criticism (13,14). More recently Ca has been shown to influence force development in glycerinated cardiac muscle fibers (15), but the important question of how Ca influences the whole forcevelocity relation in heart muscle remains a controversial issue.…”
mentioning
confidence: 99%
“…More recently Ca has been shown to influence force development in glycerinated cardiac muscle fibers (15), but the important question of how Ca influences the whole forcevelocity relation in heart muscle remains a controversial issue. From a biochemical standpoint, Katz (16) has challenged the view that in cardiac muscle Ca really affects Vmax or the maximum rate of turnover at a single myosin crossbridge, maintaining that the influence of Ca is wholly explicable in terms of the number of crossbridges it activates and that previous observations of changes in Vmax (10,12) are unreliable or attributable to an internal load.…”
mentioning
confidence: 99%
“…It represents the total myocardial wall force at zero CE shortening velocity and has been considered as a suitable measure of muscle activation [15] both with regard to its time course as to its dependency on contractile state [2,9,12]. Po was found as a result of the curve fitting procedure which in this respect acted as an extrapolation technique.…”
Section: Resultsmentioning
confidence: 99%
“…Note that for VcE = 0: F = Fo. During isometric contraction shortening velocity of the CE is related to the rate of force development by: Combining (1), (2) and (3) rate of force development before and after the QVR is found from:…”
Section: Methodsmentioning
confidence: 99%